2021
DOI: 10.1177/00222437211030685
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Lonely Increases Interest in Previously Owned Products

Abstract: Consumption of used products has the potential to symbolically connect present and previous users of these products, something that would be appealing to lonely consumers. Accordingly, across seven studies, feeling lonely increased the preference for previously owned products. Specifically, the proportion of lone shoppers was higher in a used versus a regular bookstore, lone individuals (vs. those sitting in pairs) were more likely to select a used over new product, on Valentine’s Day, people without (vs. with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Extant research investigating consumer responses to social exclusion comes from three perspectives. First, to fulfil social belongingness, excluded individuals will spend strategically to conform to the affiliation source (Mead et al, 2011), interact with anthropomorphic brands (Mourey et al, 2017), and increase their preference for previously owned products (Huang and Fishbach, 2021). Second, as exclusion produces a dampened sense of control, consumers tend to pursue riskier but potentially more profitable financial opportunities to obtain the instrumentality benefits of money (Duclos et al, 2013).…”
Section: Social Exclusion and Green Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant research investigating consumer responses to social exclusion comes from three perspectives. First, to fulfil social belongingness, excluded individuals will spend strategically to conform to the affiliation source (Mead et al, 2011), interact with anthropomorphic brands (Mourey et al, 2017), and increase their preference for previously owned products (Huang and Fishbach, 2021). Second, as exclusion produces a dampened sense of control, consumers tend to pursue riskier but potentially more profitable financial opportunities to obtain the instrumentality benefits of money (Duclos et al, 2013).…”
Section: Social Exclusion and Green Consumptionmentioning
confidence: 99%
“…, 2011), interact with anthropomorphic brands (Mourey et al. , 2017), and increase their preference for previously owned products (Huang and Fishbach, 2021). Second, as exclusion produces a dampened sense of control, consumers tend to pursue riskier but potentially more profitable financial opportunities to obtain the instrumentality benefits of money (Duclos et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Linking value is created by shared sense of ethical we-ness for sustainability. Feeling lonely intensifies consumers' liking for secondhand goods as lonely consumers' desire to symbolically connect with previous owners (Huang & Fishbach, 2021). This logic may apply to buyers and sellers closet cleaning, especially during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Used products also appear to appeal to lonely consumers because they provide a symbolic connection to previous users. Across a series of studies, Huang and Fishbach (2021) showed that both chronic and transient loneliness are positively related to preferences for used (vs. new) products, that simply being alone (sitting alone, shopping alone) is associated with greater preference for used products, and experimentally inducing temporary feelings of loneliness increases interest in consuming used products, and this effect is mediated by the desire to connect with prior owners.…”
Section: Consumer Responses To Lonelinessmentioning
confidence: 99%